2015
DOI: 10.1016/j.cub.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A Kinase Contributes to a Pole-Based Error Correction Pathway

Abstract: Summary Chromosome biorientation, where sister kinetochores attach to microtubules (MTs) from opposing spindle poles, is the configuration that best ensures equal partitioning of the genome during cell division. Erroneous kinetochore-microtubule (kt-MT) attachments are commonplace but often corrected prior to anaphase [1, 2]. Error correction, thought to be mediated primarily by the centromere-enriched Aurora B kinase (ABK) [3-5], typically occurs near spindle poles [6]; albeit, the relevance of this locale is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(166 citation statements)
references
References 54 publications
11
153
2
Order By: Relevance
“…51 Additionally, Aurora A might play other important roles in chromosome congression by regulating proteins directly involved in this process. 53,54 Two recent studies further confirmed our observation about the role of Aurora A in error correction near the poles in mitosis and also in meiosis I. Ye and colleagues 41 demonstrated the existence of an Aurora A activity gradient centered on the spindle poles in Drosophila S2 cells using a Fluorescence Resonance Energy Transfer sensor bound to microtubules that was Figure 1. Dynein "locks" peripheral chromosomes at the spindle poles after CENP-E inhibition.…”
Section: Dynein Prevents Prematuresupporting
confidence: 57%
See 2 more Smart Citations
“…51 Additionally, Aurora A might play other important roles in chromosome congression by regulating proteins directly involved in this process. 53,54 Two recent studies further confirmed our observation about the role of Aurora A in error correction near the poles in mitosis and also in meiosis I. Ye and colleagues 41 demonstrated the existence of an Aurora A activity gradient centered on the spindle poles in Drosophila S2 cells using a Fluorescence Resonance Energy Transfer sensor bound to microtubules that was Figure 1. Dynein "locks" peripheral chromosomes at the spindle poles after CENP-E inhibition.…”
Section: Dynein Prevents Prematuresupporting
confidence: 57%
“…Moreover, they used live-cell imaging to show that Mad1-GFP signal accumulated on kinetochores near the spindle pole, both in trivalents and syntelically-attached bivalents that became efficiently corrected as they approached the spindle pole. Altogether, these studies in 4 different systems 5,41,42 demonstrate that, in addition to a centromeric-based error correction mechanism mainly driven by Aurora B, an Aurora A-regulated error correction mechanism exists in the vicinity of the spindle poles to prevent the premature stabilization of end-on kinetochore microtubule attachments. This is likely to be important for subsequent CENP-E-mediated congression of polar chromosomes along preexisting spindle microtubules.…”
Section: Dynein Prevents Prematurementioning
confidence: 85%
See 1 more Smart Citation
“…Another Aurora kinase family member, Aurora A, localizes to spindle poles and phosphorylates overlapping substrates with Aurora B, including Hec1. Recently, it was reported that Aurora A also plays a role in the correction of erroneous attachments, whose dysfunction gives rise to misoriented chromosomes near the spindle poles [68,69].…”
Section: Weakened Activity Of Aurora Kinasesmentioning
confidence: 99%
“…It has been established that a gradient of Plk1 and Ran-GTP concentrations control spindle position (Kiyomitsu and Cheeseman, 2012), and Aurora A forms a spatial gradient that originates at the spindle pole (Ye et al, 2015;Hochegger et al, 2013). Abrogation of the Ran-GTP gradient that is established around aligned chromosomes using a dominant-negative RanT24N mutant has no effect on congression (Barisic et al, 2015).…”
Section: Coupling Congression With Position-sensing In the Spindlementioning
confidence: 99%